Social connectedness and healthcare engagement among adults with disabilities: The role of living arrangement - Hyun-Jun Kim; Natalie Turner; Brittany Jones-Cobb (PLoS ONE, 2026)
People with disabilities face significant healthcare engagement barriers, leading to increased risks of preventable conditions and mortality. This is particularly concerning for the quarter who live alone. Despite recognition of healthcare engagement as a social process, empirical understanding remains limited. This study examined how social connectedness predicts healthcare engagement, testing whether disability status and living arrangements moderate these associations. We analyzed data from 335 U.S. adults (ages 21–83) via an online survey. Healthcare engagement was assessed through three indicators: having a usual source of care, a personal doctor, and routine checkups. Social connectedness included intimate network size and informal health information network size. Using logistic regression, we tested main effects of social connectedness after controlling for covariates and three-way interactions (social connectedness × disability × living arrangements). Informal health information network size significantly predicted having a usual source of care and a personal doctor while intimate networks showed no main effects. A three-way interaction revealed that larger informal health information networks improved personal doctor access among adults without disabilities (regardless of living arrangements) and adults with disabilities living with others, but not among those with disabilities living alone. For routine checkups, larger intimate networks reduced utilization among adults with disabilities living alone. Social connectedness plays a conditional rather than universal role in healthcare engagement. Adults with disabilities living alone represent a particularly vulnerable population who do not benefit from social connectedness in accessing healthcare, highlighting the need for targeted interventions addressing their unique barriers.